The Essence of the Information and Communication Culture of a Primary School Teacher - Olena Lushchynska (Vasyl Stefanyk Precarpathian National University, 2022)
In the article the essence of the following concepts are analyzed and clarified: "culture" (education and upbringing level, as well as a field of competence or activity); "general culture" (a person's general characteristics); "professional culture" (an integral characteristic of a person as a specialist which determines the level of his/her  qualifications and authority in the professional environment); "pedagogical culture" (embodied in professional activities and depends on the level of society development, the teacher's competence); "information", "communication" (outlined in the spiritual and psychological context of the process of human communication, characterized by the essence and forms of psychological contact as well as influence; "information culture" (a holistic subsystem of the person's general professional culture, an indicator of the level of modern teachers' professional competence, manifested in the understanding and ability to perceive different information and use information technology to create own interactive space); "information and communication culture" (a substructure of pedagogical culture, integrating professional knowledge, skills and abilities to work in the information environment, communication activities, knowledge of professional ethics and aesthetics using the proposed and creating own information products for educational activities), etc. The essence of the information culture of the teacher is substantiated, which, according to the author, is an interconnected component of both the general culture and pedagogical culture, as well as the culture of society as a whole. The levels of information culture in the general context of digitalization of society, as well as the development of information and communication literacy of modern teachers are analyzed. The author's materials from the dissertation "Formation of information and communication culture of future primary school teachers in the process of professional training" for the degree of Doctor of Philosophy (2021) are used in the article.